Odontología para bebés - Ana María Lopez-Palacio (Universidad de Antioquia, 1999)
The baby's dentistry proyect was born as an answer to the cornunity needs in education and attention in oral health in children from birth until 5 years of age. This program enables people to understand that oral health is part of general health, it introduces sharing work between professional workers and cornunity. Makes possible selfcare, and keep health, induces multidisciplinary work, changes the general request from oral treatment to prevention so helps in the reduction of dental cavity prevalence in children.